2012
DOI: 10.1093/ser/mws017
|View full text |Cite
|
Sign up to set email alerts
|

Workforce reduction and firm performance: evidence from French firm data (1994–2000)

Abstract: Using a large annual data base of French firms (1994-2000), this article examines the determinants of a workforce reduction of publicly-listed and non-listed companies and their consequences on firm performance. Firstly, workforce reduction appears to be a defensive response to an adverse economic shock. However, publicly-listed firms anticipate better than the others the decision to cut jobs. Secondly, using a Difference in Differences model, the estimates indicate that there has been a very small but signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
5
0
5
Order By: Relevance
“…Raynaud (2012) found that reducing labour force was positively associated with increases in an organisation's ROA in both the short (one year) medium (3 years) and long term (5 years) at a steady climb. The positive result was more prominent in non-listed organisation as they give precedence to economic rather that accounting figures (Reynaud, 2013). De Meuese and Dai (2013) noted an improvement in ROTA in the year of labour force reduction and a continuous upward trend post labour force reduction reflecting the positive relationship between downsizing and firm performance.…”
Section: Labour Force Reduction Relationship With Rotamentioning
confidence: 98%
“…Raynaud (2012) found that reducing labour force was positively associated with increases in an organisation's ROA in both the short (one year) medium (3 years) and long term (5 years) at a steady climb. The positive result was more prominent in non-listed organisation as they give precedence to economic rather that accounting figures (Reynaud, 2013). De Meuese and Dai (2013) noted an improvement in ROTA in the year of labour force reduction and a continuous upward trend post labour force reduction reflecting the positive relationship between downsizing and firm performance.…”
Section: Labour Force Reduction Relationship With Rotamentioning
confidence: 98%
“…Penelitian dengan hal sejenis menemukan bahwa sifat financial distress yang memicu pengurangan tenaga kerja (Reynaud, 2012), kemudian juga menemukan pengurangan tenaga kerja tampaknya merupakan respons defensive terhadap guncangan ekonomi yang merugikan. Hasil lain (Kielselbach, 2007)menunjukkan bahwa kebangkrutan perusahaan mengarah pada perampingan yang signifikan, ketika sebuah perusahaan mengajukan kebangkrutan, karyawannya secara signifikan lebih cenderung bekerja lebih sedikit, meninggalkan perusahaan (John R Graham, Hyunseob Kim, Si li, Jiaping Qiu, 2016).…”
Section: Latar Belakangunclassified
“…Identifikasi empiris strategi pengurangan karyawan tidak selalu jelas dilakukan (Karlsson, 2012). Penelitian lain menemukan dari kelompok yang terdaftar dan tidak terdaftar di bursa efek, perusahaan yang melakukan kebijakan perampingan atau pengurangan karyawan tidak mempertahankan kinerja keuangan (ROE) (Reynaud, 2012). Penemuan selanjutnya bahwa 70% tingkat kegagalan berasal dari jawaban atas pertanyaan apakah perampingan yang dilakukan perusahaan gagal atau sukses adalah masih ambigu atau tidak jelas (Hughes, 2011).…”
Section: Latar Belakangunclassified
See 1 more Smart Citation
“…This allows for greater flexibility in operating costs, and thus protects the bottom line. However, stock market listing does not seem to be associated with workforce retention policies in the event of a strong decline in business, as shown by Reynaud (2012) and Deroyon and Romans (2014).…”
Section: Characterisation Of Establishment Typesmentioning
confidence: 99%